Characteristics of a double-swirl combustor for the thermal destruction of waste HFC refrigerants. (2018) - Ohm, Tae-In; Chae, Jong-Seong; Kim, Sin-Young; Kim, Soo-Yeon; Moon, Seung-Hyun
The use of chlorofluorocarbons and hydrochlorofluorocarbons has been banned since the Montreal Protocol. Hydrofluorocarbon (HFC) series refrigerants were developed as an alternative, but HFC-134a has been found to have a high global warming potential. Thus, an eco-friendly, economical, and stable technology for removing waste HFCs is required. Existing methods involving pyrolysis for destruction of waste HFC include incineration, catalytic oxidation, and plasma pyrolysis. In this study, an economical and eco-friendly combustor that consumes little auxiliary fuel and easily neutralising hydrofluoric acid gas was developed to destroy waste HFC-134a. The conceptual design of a double-swirl combustor was developed based on numerical simulations and used to manufacture a prototype, which was used in a combustion experiment. When the auxiliary fuel LPG was used at a flow rate of 1.0 kg/h with an air ratio of 1.1, the average temperature at the vertical section in the combustion chamber was 1, 300 K, which is sufficient to destroy waste HFCs. In the waste refrigerant destruction test, the destruction ratio of waste HFCs was 100% when waste HFCs were injected at a flow rate of 2.8 kg/h or less and 99.37% at a flow rate of 2.9 kg/h.